THE IDENTIFICATION OF SMALL MEDIUM ENTERPRISE (SME) OWNER ENTREPRENEURSHIP CHARACTERISTICS BY USING ENTREPRENEURIAL MARKETING APPROACH - Hongdiyanto, Charly (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
Economic crisis occurred in 1997 had brought continuously negative affect in economic and social aspect. This negative effect experienced by Indonesia as one of the countries in Asia region forced to survive from global economic crisis. One among many downfalls from thisunfortunate event was many big scale companies had to deal with bankruptcy. Interesting fact from this event sought by researcher was the ability of small medium enterprise (SME) to survive from economic crisis compared to other big companies. Therefore, focus to small and medium size company should be put into consideration. One of the ideas to improve the performance of SME is by implementing the concept of entrepreneurial marketing. The goal of this research is to identify characters owned by entrepreneurial marketer. Five owners of SME’s in food and beverage industry are used as the respondents in this research. In depth interview is used for the method in gaining the valuable information. Data analysis used consist of data exposure, grouping the information, analysis and make the conclusion.